2020
DOI: 10.1038/s41598-020-75995-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell MT1-MMP is dispensable for osteosarcoma tumor growth, bone degradation and lung metastasis

Abstract: The membrane-anchored matrix metalloprotease MT1-MMP is a potent collagenolytic enzyme with a well-established role in extracellular matrix turnover and cellular invasion into collagen-rich tissues. MT1-MMP is highly expressed in various types of cancer and has been demonstrated to be directly involved in several stages of tumor progression, including primary tumor growth, angiogenesis, invasion and metastasis. Osteosarcoma is the most common type of primary bone cancer. This disease is characterized by invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Osteosarcoma is a frequent malignancy in bone among children and adolescents, with an estimated incidence rate of 3 per million per year all over the world. Osteosarcoma is often accompanied with early metastasis, thus being considered as an invasive tumor [26,27]. Although radiotherapy and neo-adjuvant chemotherapy have been developing over the past years, the OS at 5 years in metastatic cases remains only about 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma is a frequent malignancy in bone among children and adolescents, with an estimated incidence rate of 3 per million per year all over the world. Osteosarcoma is often accompanied with early metastasis, thus being considered as an invasive tumor [26,27]. Although radiotherapy and neo-adjuvant chemotherapy have been developing over the past years, the OS at 5 years in metastatic cases remains only about 20%.…”
Section: Discussionmentioning
confidence: 99%
“…These cells were cultured following the recommendations from the suppliers. The osteosarcoma cell line, 143B-luc2/tom-1A6, was derived from human wildtype 143B cells (ATCC Cat# CRL-8303, RRID: CVCL_2270) as described [ 35 ]. Since these cells were used as a positive control for uPARAP expression, the short designation 143B +/+ is used for the 143B-luc2/tom-1A6 cell line in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Since these cells were used as a positive control for uPARAP expression, the short designation 143B +/+ is used for the 143B-luc2/tom-1A6 cell line in this paper. The uPARAP knock-out cell line, 143B -/-, was derived from the 143B +/+ cell line by CRISPR/Cas-9 technique, using a guide RNA targeting exon 2 of the human MRC2 gene and with design and overall editing conditions as previously described [ 17 , 35 ]. These cells, used as a negative control for uPARAP expression, are uPARAP-deficient due to a homozygous 4 nt insertion in exon 2, which encodes the first structural domain of uPARAP.…”
Section: Methodsmentioning
confidence: 99%
“…For most of the studies that imply a direct role of cancer cells in bone degradation, the strongest evidence is related to their collagenolytic activity. The expression of collagenases and gelatinases, including cathepsin K and various MMPs, in different types of cancer cells has been extensively studied [70,[80][81][82][89][90][91][92][93][94]. However, it was recently shown that depletion of the collagenase MT1-MMP/MMP14 in osteolytic osteosarcoma had no effect on cancer-induced bone degradation in an orthotopic transplanted mouse model [94].…”
Section: Involvement Of Tumor Cells In Bone Degradationmentioning
confidence: 99%
“…The expression of collagenases and gelatinases, including cathepsin K and various MMPs, in different types of cancer cells has been extensively studied [70,[80][81][82][89][90][91][92][93][94]. However, it was recently shown that depletion of the collagenase MT1-MMP/MMP14 in osteolytic osteosarcoma had no effect on cancer-induced bone degradation in an orthotopic transplanted mouse model [94]. Thus, the mere expression of collagen-degrading proteases does not necessarily implicate that the cancer cells are osteolytic and the functional significance of cancer-cell-expressed collagenolytic enzymes is likely to differ between different types of cancers.…”
Section: Involvement Of Tumor Cells In Bone Degradationmentioning
confidence: 99%